2020
DOI: 10.1016/j.cjca.2020.04.038
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Physical Activity During COVID-19 Pandemic in Children With Congenital Heart Disease

Abstract: Children with congenital heart disease (CHD) are at risk for both COVID-19 and secondary cardiovascular outcomes. Their increased cardiovascular risk may be mitigated through physical activity, but public health measures implemented for COVID-19 can make physical activity challenging. We objectively measured the impact of the COVID-19 pandemic on physical activity, continuously measured by Fitbit step counts, in children with CHD.Step counts were markedly lower in late March and early April 2020, compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(112 citation statements)
references
References 16 publications
5
101
0
6
Order By: Relevance
“…A study using prospective data from 823 adolescents around the age of 16 years in Croatia also showed that PA levels decreased and that there was a stronger decrease in adolescents living in urban areas 21 . Another study investigated step count changes in 109 children with congenital heart disease in Canada, showing that total steps decreased by 21–24% at the end of March and beginning of April 2020 as compared to the same time in 2019 22 . A study with 41 children between 6 and 18 years of age with obesity in Italy also showed that children reduced PA by almost 2.5 h per week 23 .…”
Section: Introductionmentioning
confidence: 99%
“…A study using prospective data from 823 adolescents around the age of 16 years in Croatia also showed that PA levels decreased and that there was a stronger decrease in adolescents living in urban areas 21 . Another study investigated step count changes in 109 children with congenital heart disease in Canada, showing that total steps decreased by 21–24% at the end of March and beginning of April 2020 as compared to the same time in 2019 22 . A study with 41 children between 6 and 18 years of age with obesity in Italy also showed that children reduced PA by almost 2.5 h per week 23 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in wealthier countries, quarantine, social distancing, and parental difficulties led to unhealthy lifestyle modifications among adolescents with increased consumption of unhealthy foods and reduction in physical activity that may lead to obesity and sleep disorders [98][99][100][101][102]. Suggested steps to encourage physical activity during this period include incorporating physical activity into children's daily routine, using electronic devices for engaging children to physical activity, encouraging family members to join ongoing activities, and avoiding extended sitting [101].…”
Section: Indirect Consequences On Child Healthmentioning
confidence: 99%
“…A study including 109 children with congenital heart disease showed a decrease of steps by 21-24% around March 11, when the WHO declared the COVID-19 outbreak to be a pandemic [52].…”
Section: Physical Inactivitymentioning
confidence: 99%